Hallássérült diákok idegen nyelvvel kapcsolatos egyéni változóinak vizsgálata - Csizér, Kata; Piniel, Katalin; Kontráné Hegybíró, Edit (Magyar Pedagógia, 2015)
The aim of the present study is to investigate deaf and hard-of-hearing language learners’ individual differences concerning English as a foreign language. As there are no similar studies in the Hungarian context, we felt that it was important to gain information on this particular learner group. A questionnaire was used to measure participants’ self-reported L2 motivation, language learning beliefs and strategies as well as their self-efficacy measures. 105 deaf and hard-of-hearing students from all over the country filled in the barrier-free paper-and-pen instrument. The data analysis presented in this article used correlational techniques to investigate the relationships among the scales. The most important results revealed that hearing impaired students’ motivation was lower than the motivation of similar age-groups without hearing problems. In addition to this, our data analysis showed that there were differences between the correlational patterns in the different schools. Students attending schools where the use of the Hungarian sign language is incorporated into the English language class or is accepted as part of school life exhibited significant links between modality and various individual scales, which might indicate a higher level of intended behavior as well.